3m-6=12+2m

Simple and best practice solution for 3m-6=12+2m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-6=12+2m equation:


Simplifying
3m + -6 = 12 + 2m

Reorder the terms:
-6 + 3m = 12 + 2m

Solving
-6 + 3m = 12 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
-6 + 3m + -2m = 12 + 2m + -2m

Combine like terms: 3m + -2m = 1m
-6 + 1m = 12 + 2m + -2m

Combine like terms: 2m + -2m = 0
-6 + 1m = 12 + 0
-6 + 1m = 12

Add '6' to each side of the equation.
-6 + 6 + 1m = 12 + 6

Combine like terms: -6 + 6 = 0
0 + 1m = 12 + 6
1m = 12 + 6

Combine like terms: 12 + 6 = 18
1m = 18

Divide each side by '1'.
m = 18

Simplifying
m = 18

See similar equations:

| 5n-2+3n=15 | | 5(x-2)=10x+10 | | [4x-3y-18]dy=[2y-x+7]dx | | 5t-13=-1+7t | | 0.9(x+90)+0.7=145 | | a+3.75=a^2 | | 7s-24=-30+9s | | -0.5x+6.38=-0.9+6.78 | | 3y+4=z | | y=2x^2+12x+10 | | 4x-5=5x-3 | | 400x-0.62=800x+0.86 | | y+2=-3(1+-4) | | 8.5=6x+7.6 | | -1+5t=-16 | | y-6.8=9 | | 9(y-8)=2y-44 | | 4x-23.1=x | | 8(x-4.1)=2.4 | | (X)(x)(x+6)=432 | | 2.4t+6.89=-7.03 | | -.3x+3.4=9.3 | | 25+.45x=40+25x | | -.3+3.4=9.3 | | 2.4t+6.89=7.03 | | 6x-22=56+4x | | a=2.4c+6 | | 2b+1=b+7 | | y=240+5x | | 3p+21=-6 | | y+140=5x-100 | | 4y-9=43 |

Equations solver categories